Deus é eles: práticas religiosas familiares dos imigrantes japoneses em Santa Maria/RS - Silva, Alexandra Begueristain da (2013)
This dissertation is based on fieldwork conducted among Japanese immigrants from the city of Santa Maria / RS. From this fieldwork, I tried to interpret their religious practices. Such practices are kept in the family, within home, shaped the foundations of the research and the reflections presented here. The central focus of the discussion is about the actions that can be linked to religion or custom, including ancestor worship, the sense of community relations and family. As well as the construction of an ethnic identity from the contact of the immigrant culture with brazilian culture, while adoptive country. To this goal I tried to build a historical overview of Japanese immigration to Brazil and Rio Grande do Sul until the official arrival of the first immigrants at the city of Santa Maria, considering that despite having arrived in the period after the World War II, they emigrated to Brazil with the same goal of the first immigrants which arrived in 1908, to raise funds and return to their home country in a maximum period of five years. I checked yet how these Japanese established and how they kept or not, the elements of their native culture in the host society, both in the sense of being inserted in the community, keeping diacritical traits that still identify themselves as Japanese. Through dialogue with the subjects, I could observe, by means of the memories told by them, why their religion is kept intimate and in the family, and by which adaptations they went through to turn into what they are today. With that, I tried to learn the adaptations of these practices over the years and across generations, and tried to visualize the possibilities of their continuity or not among the families with whom I interacted. Finally, after searching theoretical references to characterize the result of my interpretations of religious practices among Japanese, I propose to address the concept of "weave" culture, in which the elements are Buddhism, Shinto, Confucianism and Christianity in complementarity, without the deletion of an activity by another.